Entrepreneurial orientation in internationalised SMES: evidence from Malaysia - Chew, Tze Cheng (Global Academic Excellent, 2018)
The international entrepreneurship (IE) literatures suggest that entrepreneurial orientation (EO) enhances the performance of firms in international markets, however, theempirical results are inconclusive. Drawing on the resource-based view (RBV), this study attempts i) to examine whether EO prevails in Malaysian SMEs that compete in the world market; and ii) whether EO can be associated with the performance of the firms, in particular, international performance. The study employed a quantitative research method and conducted a large-scale, self-administered questionnaire survey in Malaysia. Drawing upon data from 203 Malaysian internationalised SME, the statistical results show that the perceived level of EO is above average level. Among the measures of EO, innovativeness is relatively higher than pro-activeness and risk-taking behaviours. Moreover, the analysis reveals the positive association of EO in the firms’ international performance. Significant practical implications are derived accordingly for business practitioners and policymakers to promote SMEs' international business development and growth.